Apple Seed to Juice - Langdo, Bryan; Neuenfeldt, Elizabeth (Minneapolis, Minnesota : Bellwether Media, Inc., 2024)
"Relevant images match informative text in this introduction to how apple seeds become juice. Intended for students in kindergarten through third grade"--
Includes bibliographical references and index.
Keywords: Apples -- Juvenile literature; Apple products -- Juvenile literature